Arabic thought beyond the liberal age : towards an intellectual history of the Nahda - Hanssen, Jens; Weiss, Max, 1977- (Cambridge : Cambridge University Press, 2016)
What is the relationship between thought and practice in the domains of language, literature and politics? Is thought the only standard by which to measure intellectual history? How did Arab intellectuals change and affect political, social, cultural and economic developments from the eighteenth to the twentieth centuries? This volume offers a fundamental overhaul and revival of modern Arab intellectual history. Using Hourani's Arabic Thought in the Liberal Age, 1798-1939 (Cambridge, 1962) as a starting point, it reassesses Arabic cultural production and political thought in the light of current scholarship and extends the analysis beyond Napoleon's invasion of Egypt and the outbreak of World War II. The chapters offer a mixture of broad-stroke history on the construction of'the Muslim world', and the emergence of the rule of law and constitutionalism in the Ottoman empire, as well as case studies on individual Arab intellectuals that illuminate the transformation of modern Arabic thought.
General introduction: Time, language, mind and freedom : the Arabic Nahda in four words / Jens Hanssen and Max Weiss -- Part I. The Legacies of Albert Hourani -- Albert Hourani and the making of modern Middle East studies in the English-speaking world : a personal memoir / Roger Owen -- Albert's world : historicism, liberal imperialism and the struggle for Palestine, 1936-48 / Jens Hanssen -- Part II. The Expansion of the Political Imagination -- Debating political community in the age of reform, rebellion and empire, 1780-1820 / Dina Rizk Khoury -- The question of the Ottoman caliphate in global Muslim political thought, 1774-1914 / Cemil Aydin -- From rule of law to constitutionalism : Arab political thought in its Ottoman context, 1808-1908 / Thomas Philipp -- Part III. Means and Ends of the Nahda Experiment -- Ahmad Faris al-Shidyaq (1804-87) : the quest for another modernity / Fawwaz Traboulsi -- Liberal thought and the'problem' of women : 1890s Cairo / Marilyn Booth --'Illiberal' thought in the liberal age : Yusuf al-Nabhani (1849-1932), dream-stories and the polemics against the modern era / Amal Ghazal -- Part IV. The Persistence of the Nahda -- Participation and critique : Arab intellectuals respond to the'Ottoman revolution' / Thomas Philipp -- Men of capital : making money, making nation in Palestine / Sherene Seikaly -- The demise of'the Liberal age'? :'Abbas Mahmud al-'Aqqad and Egyptian responses to Fascism during World War II / Israel Gershoni -- Part V. The Afterlives of the Nahda in Comparative Perspective -- Indian and Arabic thought in the liberal age / C.A. Bayly -- The autumn of the Nahda in light of the Arab Spring : some figures in the carpet / Leyla Dakhli -- Epilogue: The Legacies of Arabic Thought in the Liberal Age / Rashid Khalidi.
Title from publisher's bibliographic system (viewed on 31 Jan 2017).
Keywords: Arab countries -- Intellectual life -- 18th century; Arab countries -- Intellectual life -- 19th century; Arab countries -- Intellectual life -- 20th century; Social change -- Arab countries -- History; Muslims -- Arab countries -- Intellectual life; Intellectuals -- Arab countries -- Biography; Liberalism -- Arab countries -- History; Political science -- Arab countries -- History; Politics and literature -- Arab countries -- History; Arab countries -- Politics and government